Cooperative or collaborative literacy practices: Mapping metadiscourse in a business students’ wiki group project - Alyousef, Hesham Suleiman; Picard, Michelle Yvette (Australasian Journal of Educational Technology, 2011)
Although wikis have been used successfully in collaborative learning in higher education, there is a lack of research investigating wikis in business module assessment tasks. Little research to date has been conducted on how wikis formatively develop international English as a second language (ESL) in business students' academic discourse. In this case study, students' use of a wiki in an assessment task in the Intermediate Financial Reporting (IFR) module is examined. This study is framed by Hyland and Tse (2004) and Hyland's (2005, 2010) models for the analysis of metadiscourse markers in IFR discourse. The findings of the interviews showed that although students collaborated and cooperated together to do the task, they favoured cooperative over collaborative learning. The linguistic analysis findings showed that the use of interpersonal metadiscourse features varied in the wiki discussion pages versus the report, indicating the students' awareness of their audience and the different genres, although the textual features of the wiki discussion pages resembled those of the report. The study is significant as it is the first to explore wikis' epistemological effects on Master of Commerce students' learning and it could potentially assist in the enhancement of wikis as a learning tool in profession-related courses, particularly those with high numbers of international, ESL students.